Polydiacetylene Liposome Microarray Toward Influenza A Virus Detection: Effect of Target Size on Turn-On Signaling - Seo, Sungbaek; Lee, Jiseok; Choi, Eun-Jin; Kim, Eun-Ju; Song, Jae-Young; Kim, Jinsang (Macromolecular rapid communications., 2013)
Target size effect on the sensory signaling intensity of polydiacetylene (PDA) liposome microarrays was systematically investigated. Influenza A virus M1 peptide and M1 antibody were selected as a probe–target pair. While red fluorescence from the PDA liposome microarrays was observed when the larger M1 antibody was used as a target, when the same M1 antibody was used as a probe to detect the smaller M1 peptide sensory signal did not appear. The results reveal that the intensity of the PDA sensory signal is mainly related to the steric repulsion between probe–target complexes not the strength of the probe–target binding force. Based on this finding, we devised a PDA sensory system that directly detects influenza A whole virus as a larger target, and confirmed the target size effect on the signaling efficiency of PDA. The 2009 influenza pandemic highlighted the need for a rapid and sensitive influenza A virus detection kit. A systematically investigated polydiacetylene microarray sensor allows a turn‐on sensory signal within 1 h and comparable detection limit with conventional kits. Denser probe molecules and larger targets contribute to PDA sensitivity, providing insight for designing future PDA‐based sensors.